Vulnerability of Critical Medicine Supply Chains in Remote Islands: A System Dynamics Study in Maluku, Indonesia - Fendy Prasetyawan; Emma Jayanti Besan; Muhammad Nurul Fadel; Ika Lismayani Ilyas (Fundamental and Applied Research in Medicine and Allied Sciences Indonesia, 2025)
Ensuring the continuous availability of critical medicines in remote island regions remains a major challenge in decentralized health systems. This study examines the pharmaceutical supply chain in the remote islands of Maluku Province, Indonesia, through a supply chain mapping and vulnerability analysis using a System Dynamics (SD) approach. The findings indicate that fragmented governance structures, combined with extreme geographical dispersion, generate persistent vulnerabilities across procurement, distribution, and service delivery levels. Key reinforcing mechanisms driving medicine stockouts include delayed quantification and procurement processes, logistical bottlenecks in inter-island transportation, and shortages of skilled pharmaceutical personnel. The analysis further shows that interventions focused solely at the health facility level are insufficient to resolve systemic weaknesses. Instead, strengthening medicine security in Maluku requires integrated strategies at higher administrative levels, including investment in human capital, diversification of supply routes, strategic buffer management, and the use of transparent, data-driven logistics information systems. By adopting a systems-based analytical framework, this study provides evidence to support more resilient policy design for improving equitable access to essential medicines in Eastern Indonesia.